2009
DOI: 10.2174/157340509789000589
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Modulation of Central Neural Pathway Underlying Acupuncture Action: A Systematic Review

Abstract: Acupuncture, an ancient therapeutic technique, is currently gaining popularity as an important modality of alternative and complementary medicine in the West world. Concurrently, scientific interests in exploring whether acupuncture is therapeutically effective are raised alongside those about the means by which it may operate. Modern neuroimaging techniques such as functional magnetic resonance imaging, positron emission tomography, electroencephalography, and magnetoencephalography provide a means to safely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 65 publications
1
4
1
Order By: Relevance
“…Activity observed in the cerebellar nodulus and uvula in this study was consistent with recent reports of neural responses following acupuncture at PC6 (6), whereas the hemodynamic neural response was in an opposite direction. Although this inconsistency between our findings and our predecessors may partly be due to various inherent factors in the fMRI experiments (different needling methods and diverse intensities of acupuncture stimulation), such varied detected hemodynamic response may also be attributed to the presence of significant activities during the sequential resting epoch (31, 32). Response magnitudes of some part of the cerebellar during the PARS were even higher than that of the stimulation epoch (Table 1).…”
Section: Discussioncontrasting
confidence: 95%
“…Activity observed in the cerebellar nodulus and uvula in this study was consistent with recent reports of neural responses following acupuncture at PC6 (6), whereas the hemodynamic neural response was in an opposite direction. Although this inconsistency between our findings and our predecessors may partly be due to various inherent factors in the fMRI experiments (different needling methods and diverse intensities of acupuncture stimulation), such varied detected hemodynamic response may also be attributed to the presence of significant activities during the sequential resting epoch (31, 32). Response magnitudes of some part of the cerebellar during the PARS were even higher than that of the stimulation epoch (Table 1).…”
Section: Discussioncontrasting
confidence: 95%
“…The sustained effects of acupuncture have been widely applied to clinical treatment; thus, we assumed that the relatively functional specificity of acupoints may evolve as a function of time. Some studies have already paid attention to the sustained effects of acupuncture (9, 13–16), and explored its impact on the resting‐state networks (RSNs) (17–19). Extensive signal attenuations evoked by acupuncture are observed in the core areas of the “default mode” network (DMN) (17).…”
mentioning
confidence: 99%
“…Several studies have begun to gaze on the modulatory effect of acupuncture on the resting brain networks, primarily using the functional connectivity analysis (8–12). Popular functional connectivity analysis primarily focused on the correlation patterns between a seed region and any other brain structures throughout the whole brain, depicting brain networks related to certain functions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have paid attention to the sustained effect of the acupuncture and its influence on the poststimulus resting state networks (8–12). Dhond et al revealed that acupuncture can influence intrinsic connectivity in the resting brain networks, i.e., default mode network (11).…”
mentioning
confidence: 99%